(untitled) (Proceedings of Faculty of Civil Engineering, 2024)
The dynamic response of long structures is the result of varying excitation of distant supports, which can increase the contribution of asymmetrical oscillation modes. Experimental-numerical research was carried out - in the experiments, the excitation was applied by shaking tables perpendicular to the longitudinal axis of the model, and the behavior was monitored optically, while the numerical model is based on linear FEM and numerical time integration.